1999
DOI: 10.1016/s0741-5214(99)70304-6
|View full text |Cite
|
Sign up to set email alerts
|

Arterial aneurysms in patients infected with human immunodeficiency virus: A distinct clinicopathology entity?

Abstract: Arterial aneurysms have only recently been associated with the human immunodeficiency virus (HIV). The clinical and pathological features of 10 HIV-positive patients with arterial aneurysms were retrospectively evaluated. These aneurysms were unusual in that they affected young black patients, occurred in atypical sites, and tended toward multiplicity. Surgery was performed in eight patients. Acute and chronic inflammatory changes were revealed by means of histologic examination of the aneurysm walls, with occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 13 publications
3
75
0
Order By: Relevance
“…5 HIV-associated aneurysms are a distinct clinical entity, generally occurring in younger patients who frequently lack common risk factors for aneurysmal disease. 6 They also tend to be saccular, multiple, are most commonly in the carotid and superficial femoral arteries, and affect the aorta much less frequently than atherosclerotic aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…5 HIV-associated aneurysms are a distinct clinical entity, generally occurring in younger patients who frequently lack common risk factors for aneurysmal disease. 6 They also tend to be saccular, multiple, are most commonly in the carotid and superficial femoral arteries, and affect the aorta much less frequently than atherosclerotic aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…There may be another mechanism, in which previous infections of ulcerated atherosclerotic plaque are amplified and destroy the arterial wall, resulting in aneurysms 7 . Nair et al 8 , however, found that culture was positive in only two cases of a series of ten patients with HIV and arterial aneurysms.…”
Section: Discussionmentioning
confidence: 96%
“…(52) Nair et al (53,54) (1997, 2000) encountered these entities locally: they felt that the histological similarities in the 2 conditions would have "a common pathogenetic event". In the absence of micro-organisms and atherosclerosis, it was suggested that the virus might directly involve the vessel.…”
Section: Vascularmentioning
confidence: 99%